Analysis of Learning to Make Salted Eggs as an Effort to Introduce Local Wisdom Values at RA Tahdzibul Fuad - Irmawati; Muhammad Alim Kahfi; Mahmudah; Luthfatul Laeli Nur'Afita; Nurul Pertiwi Dwi Widiatin; Sri Harti; Nazihah (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to analyze the learning of making salted eggs as an effort to introduce local wisdom values at RA Tahdzibul Fuad. This study uses a descriptive qualitative approach with a case study design to analyze the implementation of learning to make salted eggs at RA Tahdzibul Fuad. Data collection techniques through observation, interviews, and documentation. The subjects of the study included students, educators, and parents. The learning process is designed based on direct practice to increase children's involvement in understanding the process of making salted eggs while instilling local wisdom values, such as hard work, responsibility, and cooperation. The study's results showed that this activity was effective in building children's understanding of local culture and supporting the development of their motoric, cognitive, and socio-emotional aspects. Children showed high enthusiasm during learning, while support from educators and the active involvement of parents helped strengthen the effectiveness of this program. The local wisdom values found in this study include Hard Work (Effort and Diligence), Mutual Cooperation and Cooperation, Patience and Accuracy, Respecting and Preserving Local Culture, Responsibility, Love of Nature and Creativity and Innovation. This study concludes that local wisdom-based learning, such as making salted eggs, can be an innovative and relevant learning model to support the development of positive character and cultural awareness in early childhood.